Frequency of low BMD and associated risk factors in patients with inflammatory bowel disease - Saha, Chinmoy; Kabir, M. Anwarul; Ghosh, Chanchal Kumar; Saha, Ishita; Islam, M. Khademul; Chowdhury, M. Fazlul Karim; Das, Nimai; Tanjum, Tasmia (International Journal of Research in Medical Sciences, 2024)
Background: Low bone mineral density (BMD) is a known complication of inflammatory bowel disease (IBD), with several factors contributing to its occurrence. This study aims to assess the frequency of BMD and identify associated risk factors in patients with IBD. The aim of this study was to determine the frequency of low BMD and identify associated risk factors in patients with inflammatory bowel disease (IBD). Methods: This cross-sectional study included 90 patients with established inflammatory bowel disease (IBD) at the Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from June 2019 to September 2020. Patients aged 18 years and older, currently on IBD medication, were enrolled. Data on BMD, disease characteristics, and demographic factors were collected and analyzed using SPSS version 23.0. Results: Among 90 IBD patients (mean age 31.8 years, 74.4% male, 35.6% with Crohn's), 40% were smokers. BMD results showed 34.4% normal, 40% osteopenia, and 25.6% osteoporosis. Low BMD was linked to lower BMI (20.25kg/m²) and vitamin D levels (17.45ng/ml), with regression analysis confirming vitamin D deficiency as the only independent risk factor. Conclusions: Our study underscores the high prevalence of osteopenia and osteoporosis in Bangladeshi IBD patients, highlighting the critical need for regular monitoring and intervention focused on modifiable risk factors like BMI and vitamin D to safeguard bone health.